Faktor Yang Berhubungan Dengan Status Gizi Balita (Bawah Lima Tahun) di Wilayah Kerja Puskesmas Naioni Kota Kupang - Far Far, Gracia Ch. G; Nur, Marselinus Laga; Takaeb, Afrona E.L (Yayasan Literasi Sains Indonesia, 2023)
Inadequate Nutritional status of Children under five is still a public health issue in Kupang City. The purpose of this study was to analyze factors related to the nutritional status of toddlers (under five years) in the working area of ​​the Naioni Health Center, Kupang City. This study used an analytic observational method with a cross sectional study approach. The total sample of 93 people was selected using the cluster random sampling technique. The results of bivariate analysis using the chi-square test showed that there was a significant relationship between mother's knowledge and toddler nutritional status (p-value=0.024), mother's education (p-value=0.003), family income (p-value=0.005), exclusive breastfeeding (p-value=0.010), and a history of infectious diseases (p-value=0.019). Mother's knowledge is the most related factor to the nutritional status of toddlers. The variable that has no significant relationship is the mother's occupation (p-value = 0.138). Therefore the conclusion of this research is mother’s knowledge, mother’ level of health education, family income, and exclusive breast feeding are variables which have significant relationship with toddles nutritional status while mother’s occupation is a variable which has no relationship with toddler nutritional status in Naioni Health Centre. It is suggested to the health officer to increase health promotion about nutritional status to the community.